PELAKSANAAN PEMBINAAN TERHADAP ANAK BERHADAPAN DENGAN HUKUM YANG MELAKUKAN PELANGGARAN DISIPLIN PADA LEMBAGA PEMBINAAN KHUSUS ANAK KELAS II KARANGASEM - Rimbawa, I Made Artha; Kayuan, Putu Chandra Kinandana; Puspitaningrat, I Dewa Agung Ayu Mas (Fakultas Hukum Universitas Ngurah Rai, 2023)
Based on Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA) inarticle 1 paragraph 2 it is stated that a child in conflict with the law is a child who is 12 (twelve) yearsold, but not yet 18 (eighteen) years old who is undergoing treatment. his criminal period at The SpecialChild Development Institution. The issue of violations committed by children in conflict with the law at TheSpecial Child Development Institution. is nothing new, while the types of disciplinary violations can bedivided into 7 (seven) categories, namely: Legal Discipline, Moral Discipline, Environmental Discipline,Discipline of Goods and Equipment, Discipline of Ethics and Courtesy of Association, Discipline of MoneyCirculation and Discipline of Service. The implementation of guidance for Children in Conflict with theLaw who violates discipline is aimed at building positive behavior for children, protecting the safety of children, officers and the community. The coaching atmosphere that is carried out is directed at a model that encourages positive behavior, and does not only focus on the application of sanctions asa consequenceof negative behavior. The main factors found as obstacles in the implementation of guidance for Childrenin Conflict with the Law at The Special Child Development Institution Class II Karangasem are limitedfacilities & infrastructure, as well as efforts that have been made to minimize these obstacles, namelysubmitting a budget for the procurement of facilities &infrastructure and collaborating with relevantagencies.